Handbook of research on digital information technologies innovations, methods, and ethical issues - Hansson, Thomas (Hershey, PA : Information Science Reference, 2008)
'This book provides a collection of successful designs, defined as communicative relation-building solutions, for individuals and collectives of interlocutors. It includes a longitudinal perspective of past mistakes, current trends and future opportunities, and is a must-have for beginners in the field as well as qualified professionals exploring the full potential of human interactions'--Provided by publisher.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Communication and technology; Educational technology; Information technology; Electronic books; Electronic books